(untitled) (Scientific journal of the Fergana State University, 2024)
The translation and explanation of expressions conveying spatial and temporal meaning in English and Uzbek within the framework of national linguistic specificity, as well as the presentation of translations of lexico-semantic affixes that convey location meanings in Uzbek and English languages, were considered with a focus on relevant research in this field, accompanied by necessary examples. In general, the presence of space-forming affixes ensures the further expansion of vocabulary in linguistics.